Paediatric ventricular assist devices: current achievements (Swiss Medical Weekly, 2013)
In chronic cardiomyopathy, mechanical circulatory support plays an increasingly important role for children as the shortage of suitable donor hearts increases times on the transplant waiting list. Ventricular assist devices (VADs) for adults have evolved dramatically over the last decade, both as a bridge to transplantation and for permanent support. In contrast, VADs designed for children, especially for all age groups, are still in their infancy. The Medos HIA and the Berlin Heart Excor are specially designed for children with a body surface area